A randomized controlled trial of anodal transcranial direct current stimulation (A-tDCS) and olfactory training in persistent COVID-19 anosmia - Lucilla Vestito; Marta Ponzano; Laura Mori; Carlo Trompetto; Fabio Bandini; Riccardo Canta; Anna De Giovanni; Simone Strano; Andrea Pagani (Brain Stimulation)
Background: Persistent anosmia due to COVID-19 affects approximately 20 million individuals worldwide, with a serious detrimental effect on their quality of life. Effective treatments remain lacking, with olfactory training (OT) being supported by some evidence of benefit. We implemented a double-blind, randomized, controlled trial (RCT) combining OT with Anodal transcranial Direct Current Stimulation (A-tDCS) with the aim to confirm the encouraging results of a preliminary study by our group. We also evaluated the long-term effectiveness of this intervention at both one- and six-months post-treatment assessments. Methods: This RCT involved 52 patients with persistent hypo/anosmia due to COVID-19. Participants were randomly assigned to undergo OT coupled with either A-tDCS targeting the Prefrontal Cortex (PFC) (experimental group, n = 35), or sham stimulation (placebo group, n = 17) for two weeks (10 sessions). The end point was the change in smell function from the baseline, as assessed by subjective and objective scores (VAS and Sniffin' Sticks test or SST). Results: The experimental group demonstrated a significant amelioration of both smell measures. Specifically, the mean VAS-smell increased from 2.56 to 4.70 (p < 0.001) and the mean SST from 6.97 to 9.69 (p < 0.001). Seventy-seven percent of patients in the experimental group significantly improved, with 63 % achieving a complete recovery. No olfactory amelioration was observed in the placebo group. The significant smell improvement was sustained at both follow-up assessments. Conclusion: This RCT demonstrates that combining A-tDCS with concurrent OT is able to restore the olfactory function in individuals suffering from persistent COVID-19 anosmia, with a durable effect. This safe and inexpensive treatment can therefore represent a suitable and widespread option for millions of individuals. These positive results also support the hypothesis that the brain olfactory networks are involved in the pathophysiology of COVID-19 anosmia.